Pembelajaran Mufradat Melalui Media Wordwall dalam Meningkatkan Minat Belajar Bahasa Arab di MTsN 2 Magetan - Majid, Rizqi Faridah; Dudung Hamdun (Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2024)
The mastery of mufradat is one of the most important elements in Arabic language learning. However, the process of mufradat learning is often boring for students because it tends to be theoretical and requires them to memorize without practical application. The study aims to test the effectiveness of using wordwall media, a game-based application that can be accessed through a website. The research use a quantitative method with pre-experimental design, one group pretest-posttest design. The sample consisted of a class of the 8th grade MTsN 2 Magetan. Data is collected through a questionnaire and analyzed by using a paired sample t test. The results of the study showed that the use of wordwall media significantly increased student’s interest in learning with a t test score below 0.05, which is 0.020. The average pre-test score was 63.96, while the average posttest score rose to 66.86. The use of wordwall as a mufradat learning evaluation medium has proven to be effective in increasing student learning interests and shows that technology-based learning media can be an interesting and effective alternative in the Arabic language learning process. It also enriches the reference of technology based learning media in the world of education.